173k views
7 votes
Solve for z in the equation​

Solve for z in the equation​-example-1

2 Answers

9 votes

Answer:

3rd option

Explanation:

v² = w² +
(z^2)/(4) ( subtract w² from both sides )

v² - w² =
(z^2)/(4) ( multiply both sides by 4 to clear the fraction )

4(v² - w²) = z² ( take square root of both sides )


√(4(v^2-w^2)) = z

User Erhhung
by
5.0k points
2 votes

Answer:

the answer is C

Explanation:

added in the picture

Solve for z in the equation​-example-1
User Ncx
by
5.5k points